Terapi Antikoagulan pada COVID-19 - Jane Chaerub (Cermin Dunia Kedokteran, 2021)
Coronavirus disease-2019 (COVID-19) yang disebabkan infeksi Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) terutama bermanifestasi sebagai infeksi pernapasan, dengan salah satu komplikasi gangguan pembekuan darah yang dapat menyebabkan kesakitan hingga kematian. Dijumpai aktivasi kaskade koagulasi tidak terkontrol akibat berbagai efek sitokin proinflamasi yang dapat menyebabkan koagulopati konsumtif termasuk sepsis induced coagulopathy (SIC) dan disseminated intravascular coagulation (DIC). Unfractionated heparin (UFH) dan low-molecular-weight heparin (LMWH) secara umum digunakan sebagai terapi pasien COVID-19. Fondaparinux dapat menjadi alternatif untuk pasien COVID-19 rawat inap. Tromboprofilaksis extended dengan LMWH atau direct oral anticoagulants (DOAC) harus dipertimbangkan pada pasien COVID-19 dengan risiko perdarahan rendah. Coronavirus disease-2019 (COVID-19) caused by Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) mainly manifests as a respiratory infection, with complications of blood clotting disorders in severe infection which can cause severe illness to death. Uncontrolled activation of the coagulation cascade due to various effects of proinflammatory cytokines can result inconsumptive coagulopathy. Coagulation disorders can occur including sepsis-induced coagulopathy (SIC) and disseminated intravascular coagulation (DIC). Unfractionated heparin (UFH) and lowmolecular-weight heparin (LMWH) are widely used in the management of COVID-19 patients. Fondaparinux may be an alternative. Extended thromboprophylaxis with LMWH or direct oral anticoagulants (DOAC) with a low risk of bleeding should be considered in COVID-19 patients.